2021
DOI: 10.1002/admi.202101682
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Ion Transport via Dielectric Nanocube Interface

Abstract: Drastic enhancement in the high‐rate capability of lithium‐ion batteries to the level of supercapacitors while maintaining high energy density is required for next‐generation power sources. Incorporating dielectric BaTiO3 (BTO)‐based nanocubes (NCs) into the active materials–electrolyte interface provides an ultrafast charge transfer pathway via the dielectric layer. The highly dispersed NC‐decorated LiCoO2 (LCO) treated at the optimized temperature of 600 °C displays significantly enhanced high‐rate capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…TPI density is the key structural factor determining charge accumulation in the dielectric-modified AC. Increased TPI density substantially improves the high rate capability of conventional LIBs. Here, we investigated the relationships between TPI density and the resulting electric capacities for the BT-AC system. BTs with mean particle sizes of 30, 50, and 100 nm were used for the measurements.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…TPI density is the key structural factor determining charge accumulation in the dielectric-modified AC. Increased TPI density substantially improves the high rate capability of conventional LIBs. Here, we investigated the relationships between TPI density and the resulting electric capacities for the BT-AC system. BTs with mean particle sizes of 30, 50, and 100 nm were used for the measurements.…”
Section: Results and Analysismentioning
confidence: 99%
“…d EDL depends on the desolvated Li concentration; thus, increased naked Li + ion density yields a thinner EDL and greater cell capacitance. Additionally, solvated Li + ions exhibit infrequent diffusion into AC micropores because the solvated ion size is comparably larger than the pore diameter. Accordingly, it is important to enhance the desolvation activities of carrier ions to strengthen the capacities of AC-based electrodes. In conventional LIBs, the high rate characteristics of LiCoO 2 (LCO) were substantially improved by the incorporation of a BaTiO 3 (BT)-based dielectric layer as an artificial solid electrolyte interface. Indeed, when an ethylene carbonate (EC)-based electrolyte is used, the activated desolvation of Li + from (EC) 4 molecular coordinates delivers more rapid charge transport at the LCO–electrolyte interface, resulting in significant enhancement of the high rate capabilities of the LCO . Here, we demonstrate a novel charge-transfer architecture enabling the accumulation of activated ions into AC micropores via the dielectric layer.…”
Section: Introductionmentioning
confidence: 98%
“…The results showed that as TPI density increases, NC-LCO exhibits significantly enhanced high-rate performance, maintaining 56.7 mA h g À1 at 50C. 93 In conclusion, the significant improvement in rate performance can be attributed to TPI. Most of the Li + at TPI effectively participates in redox reactions, accelerating the rapid transfer of Li + .…”
mentioning
confidence: 83%